2(4c-1)-3=6c+7

Simple and best practice solution for 2(4c-1)-3=6c+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(4c-1)-3=6c+7 equation:


Simplifying
2(4c + -1) + -3 = 6c + 7

Reorder the terms:
2(-1 + 4c) + -3 = 6c + 7
(-1 * 2 + 4c * 2) + -3 = 6c + 7
(-2 + 8c) + -3 = 6c + 7

Reorder the terms:
-2 + -3 + 8c = 6c + 7

Combine like terms: -2 + -3 = -5
-5 + 8c = 6c + 7

Reorder the terms:
-5 + 8c = 7 + 6c

Solving
-5 + 8c = 7 + 6c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-6c' to each side of the equation.
-5 + 8c + -6c = 7 + 6c + -6c

Combine like terms: 8c + -6c = 2c
-5 + 2c = 7 + 6c + -6c

Combine like terms: 6c + -6c = 0
-5 + 2c = 7 + 0
-5 + 2c = 7

Add '5' to each side of the equation.
-5 + 5 + 2c = 7 + 5

Combine like terms: -5 + 5 = 0
0 + 2c = 7 + 5
2c = 7 + 5

Combine like terms: 7 + 5 = 12
2c = 12

Divide each side by '2'.
c = 6

Simplifying
c = 6

See similar equations:

| 128=3X+7(X+4) | | 3y+20=2-3y | | 168=6X+6(2X+13) | | y+2x=120 | | 7n=6+5n | | x+2y=120 | | 4=-3/5+x | | 96=6X+3(2X-4) | | w+3/8=-3/4 | | n^3-4n^2+2n-8= | | 4X+3(X+10)=72 | | w-2/5=-1/2 | | -1550-7x=-0 | | 92=4X+4(X+5) | | 7t+13=5-t | | -k+3=5-9k+7k | | 7X+7(2X-6)=105 | | 14-8-9a+10a=9a-6a | | y=50+3x | | 14-8-9a+10a=9a-6 | | 153=2X+3(7X-18) | | n*6-4=40 | | 4X+5(3X+3)=110 | | wx-w=6 | | 15+x-3+2x=2x+4x | | 4(3a-1)+11=2(6a+5)-8 | | -9(x-1)=3x-39 | | -2+7a+6=5a+4+2a | | 2v+18=-4(v-9) | | x+6=-2-2x+4x | | 0.4a+0.2=4.2a-7.8-0.6a | | 2(u-8)=8u+20 |

Equations solver categories